A Review on the Magnetorheological Fluid, Damper and Its Applications for Seismic Mitigation - Cruze, Daniel; G, Hemalatha; Jebadurai, S. Vincent Sam; L, Sarala; D, Tensing; Christy, S. S. Judith Emiliah (Salehan Institute of Higher Education, 2018)
Magnetorheological (MR) fluids and dampers have wide advances as smart materials because of its unique properties, notably, viscosity increases in the presence when magnetic field applied MR Fluids composed of three key components, including carrier fluid, surfactants and metal particles. The major applications of MR Fluids are in brakes, dampers, journal bearings, fluid clutches, pneumatic artificial muscles, aerospace etc. where electrical energy is converted to mechanical energy (Damping Force) in a controlled manner. Within a few milliseconds the fluid converts from liquid to semi solid state. Over the years, researchers were concerned on the ways to enhance the modelling precision. Though the proposed Dynamic models of MR Dampers represent displacement and force behaviour. In this review paper, the advances of MR Fluids, MR Damper, Damper Models, Energy harvesting and their applications for seismic resistance of structures are briefly discussed in the present study.